THE EFFECT OF SERVICE QUALITY, FOOD QUALITY, AND CUSTOMERS EXPERIENCE TOWARD CUSTOMERS SATISFACTION AT KOKI SUNDA MEDAN - Lin, Vivian; Alfonsius, Alfonsius (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
Koki Sunda Medan has a 4.4 rating in Google Review, which means there are many dissatisfied customers, and most of them complain about unprofessional services from staff, food is served cold and undercooked, and customers are not having a good time. Hence, this research aims to analyze if service quality, food quality, and customer experience affect customer satisfaction at Koki Sunda Medan. Data sources are primary and secondary. The technique is convenience sampling and surveys 100 participants who have visited and purchased in Koki Sunda Medan. The model of this research is multiple linear regression. The research outcomes are that service quality has a partial effect on customer satisfaction, food quality has a partial effect on customer satisfaction, and customer experience partially affects customer satisfaction. Service quality, food quality, and customer experience simultaneously affect customer satisfaction at Koki Sunda Medan. This research recommends enhancing staff alertness, installing appliances and complimentary dishes, and holding activities for customers to create memorable experiences.